Isolation and characterization of the cDNA for murine granulocyte colony-stimulating factor. - Tsuchiya, M (1986)
A cDNA sequence coding for murine granulocyte colony-stimulating factor (G-CSF) has been isolated from a cDNA library prepared with mRNA derived from murine fibrosarcoma NFSA cells, which produce G-CSF constitutively. Identification of murine G-CSF cDNA was based on the cross-hybridization with human G-CSF cDNA under a low-stringency condition. The cDNA can encode a polypeptide consisting of a 30-amino acid signal sequence, followed by a mature G-CSF sequence of 178 amino acids with a calculated Mr of 19,061. The nucleotide sequence and the deduced amino acid sequence of murine G-CSF cDNA were 69.3% and 72.6% homologous, respectively, to the corresponding sequences of human G-CSF cDNA. The murine G-CSF cDNA, when introduced into monkey COS cells under the simian virus 40 promoter, could direct the synthesis of a protein that can stimulate the granulocyte colony formation from mouse bone marrow cells and support the proliferation of murine NFS-60 myeloid leukemia cells.